Interrelationships between environmental psychological factors and environmental behaviour among Malaysians - Neo, Sau Mei (2019)
The facilities management profession has been extended to engage with issues o f sustainability and environmental degradation mostly caused by human activities such as energy consumption, water wastage, solid waste generation and air pollution. Previous studies suggested that environmental behaviour is influenced by a series o f psychological factors. Understanding the interrelationship between these factors and the behaviour in the local context will help policy maker form better strategies to improve environmental behaviour among Malaysians. Furthermore, such studies are currently absent. To address these issues, this research identified environmental psychological factors that influence environmental behaviour. Next, an investigation on the interrelationship between environmental psychological factors and environmental behaviours pertaining to the four major environmental issues, namely water, air, solid waste and climate change were conducted. Finally, significant differences in the influence o f the environmental psychological factors on environmental behaviours across urban and rural community were examined. In the research, a nationwide survey was conducted in 13 states and 3 federal territories in Malaysia. The sampling method used was multistage stratified random sampling. 6616 questionnaires from respondents across different demographics of Malaysians were collected. Structural Equation Modelling (SEM) was used to illustrate the interrelationship of the affecting environmental psychological factors and environmental behaviours (water quality conservation behaviour, air quality conservation behaviour, solid waste reduction behaviour and low carbon behaviour). In addition, Multigroup Analysis (PLS-MGA) was conducted to compare these interrelationships across urban and rural groups. Findings revealed that the environmental awareness, concern and attitude were significant and positively related to corresponding behaviours. Notably, the environmental concern was the most influencing factor to determine water and air quality conservation behaviours as well as the low carbon behaviour. Besides, awareness of water pollution and climate change towards their corresponding behaviours; and concerns towards the water and air quality conservation behaviour were significantly different across the urban and rural residents. The findings would be beneficial for government and nongovernment agencies to form better environmental policy and decision making, especially in fostering positive environmental behaviour among Malaysians.